2014
DOI: 10.1007/s00441-014-2058-7
|View full text |Cite
|
Sign up to set email alerts
|

Homolog of allograft inflammatory factor-1 induces macrophage migration during innate immune response in leech

Abstract: Allograft inflammatory factor-1 (AIF-1) is a 17-kDa cytokine-inducible calcium-binding protein that, in vertebrates, plays an important role in the allograft immune response. Its expression is mostly limited to the monocyte/macrophage lineage. Until recently, AIF-1 was assumed to be a novel molecule involved in inflammatory responses. To clarify this aspect, we have investigated the expression of AIF-1 after bacterial challenge and its potential role in regulating the innate immune response in an invertebrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…As previously demonstrated [2, 3], double immunofluorescence assays confirmed that the two proteins are constitutively expressed in unlesioned (Fig. 5a) and in PBS-injected animals (Fig.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…As previously demonstrated [2, 3], double immunofluorescence assays confirmed that the two proteins are constitutively expressed in unlesioned (Fig. 5a) and in PBS-injected animals (Fig.…”
Section: Resultssupporting
confidence: 87%
“…We have previously reported that AIF-1 and RNASET2 are significantly upregulated at 6 and 24 h following LPS injection, and that this change in their expression is involved in leech macrophage recruitment [2, 3]. However, the underlying mechanisms by which these two factors operate are still poorly characterized.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations